PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON INVESTMENT, PRICE BOOK VALUE, DAN TOTAL ASSETS TURN OVER TERHADAP KEBIJAKAN DIVIDEN (Studi Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Safina Syabani Aisyah; Atim Djazuli (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The manufacturing company is a major industrial development in Indonesia as well as in terms of dividend policy . This study aims to determine whether there are significant Earning Per Share , Debt to Equity Ratio , Return on Investment , Price Book Value and Total Assets Turn Over to the Dividend Policy . This research is explanatory research . The population of this research is manufacturing companies listed in Indonesia Stock Exchange . These samples included 30 companies that obtained by using purposive sampling method . The analytical method used is multiple regression analysis . F-test and t test studies show that the Earning Per Share , Debt to Equity Ratio, Return on Investment , Price Book Value and Total Assets Turn Over significant positive effect on Dividend Policy . While variable Earning Per Share is the most dominant variable effect on Dividend Policy .` Keywords:Earning Per Share, Debt Equity Ratio, Return On Investment, Price Book Value dan Total Asset Turn Over